14‐3‐3 proteins regulate photomorphogenesis by facilitating light‐induced degradation of PIF3. Issue 1 (30th September 2022) - Song, Pengyu; Yang, Zidan; Guo, Can; Han, Run; Wang, Huaichang; Dong, Jie; Kang, Dingming; Guo, Yan; Yang, Shuhua; Li, Jigang
Summary: 14‐3‐3s are highly conserved phosphopeptide‐binding proteins that play important roles in various developmental and signaling pathways in plants. However, although protein phosphorylation has been proven to be a key mechanism for regulating many pivotal components of the light signaling pathway, the role of 14‐3‐3 proteins in photomorphogenesis remains largely obscure. PHYTOCHROME‐INTERACTING FACTOR3 (PIF3) is an extensively studied transcription factor repressing photomorphogenesis, and it is well‐established that upon red (R) light exposure, photo‐activated phytochrome B (phyB) interacts with PIF3 and induces its rapid phosphorylation and degradation. PHOTOREGULATORY PROTEIN KINASES (PPKs), a family of nuclear protein kinases, interact with phyB and PIF3 in R light and mediate multisite phosphorylation of PIF3 in vivo . Here, we report that two members of the 14‐3‐3 protein family, 14‐3‐3λ and κ, bind to a serine residue in the bHLH domain of PIF3 that can be phosphorylated by PPKs, and act as key positive regulators of R light‐induced photomorphogenesis. Moreover, 14‐3‐3λ and κ preferentially interact with photo‐activated phyB and promote the phyB‐PIF3‐PPK complex formation, thereby facilitating phyB‐induced phosphorylation and degradation of PIF3 upon R light exposure. Together, our data demonstrate that 14‐3‐3λ and κ work in close concert with the phyB‐PIF3 module to regulate light signaling in Arabidopsis.